Core–Shell MOF‐in‐MOF Nanopore Bifunctional Host of Electrolyte for High‐Performance Solid‐State Lithium Batteries. Issue 8 (25th June 2021) - Abdelmaoula, Ahmed Eissa; Shu, Jun; Cheng, Yu; Xu, Lin; Zhang, Gang; Xia, Yangyang; Tahir, Muhammad; Wu, Peijie; Mai, Liqiang
Abstract: Solid‐state lithium‐ion batteries with high safety are the encouraging next‐generation rechargeable electrochemical energy storage devices. Yet, low Li + conductivity of solid electrolyte and instability of solid–solid interface are the key issues hampering the practicability of the solid electrolyte. In this research, core–shell MOF‐in‐MOF nanopores UIO‐66@67 are proposed as a unique bifunctional host of ionic liquid (IL) to fabricate core–shell ionic liquid–solid electrolyte (CSIL). In the current design of CSIL, the shell structure (UIO‐67) has a large pore size and a high specific surface area, boosting the absorption amount of ionic liquid electrolyte, thus increasing the ionic conductivity. Nevertheless, the core structure (UIO‐66) has a small pore size compared to the ionic liquid, which can confine the large ions, decreasing their mobility, and selectively boost the transport of Li + . The CSIL solid electrolyte exhibits considerable enhancement in the lithium transference number ( t Li + ) and ionic conductivity compared to the homogenous porous host (pure UIO‐66 and UIO‐67). Additionally, the Li|CSIL|Li symmetric batteries maintain a stable polarization of less than 28 mV for more than 1000 h at 1000 µA cm −2 . Overall, the results demonstrate the concept of core–shell MOF‐in‐MOF nanopores as a promising bifunctional host of electrolytes for solid‐state or quasi‐solid‐state rechargeable batteries. Abstract : Demonstration of continued channel (ionic pathway) within the adjacent particles of CSIL and nanowetted interfacial mechanism of the solid electrolyte with a zoom view of transference of Li + and confinement of ([EMIM] + and [TFSI] − ) by core‐shell channel. Rate performance with Coulombic efficiency of Li/CSIL/LFP batteries under different current rates (0.2, 0.4, 0.6, 0.8, 1.0, 1.5, 0.2 C) at 25 °C.